Climate change as a security issue in the Western Balkans - Stojkovski, Ljupcho; Brsakoska Bazerkoska, Julija (Ministry of Defence, Republic of North Macedonia, 2024)
Climate change is a global challenge with direct environmental, political and socioeconomic repercussions for countries and peoples around the world. It is a direct threat, for example, to the territories of some states due to rising sea levels or fires and droughts, but is also a “threat” or a “risk” multiplier, undermining food security, energy security, economic security and access to fundamental natural resources, while also impacting the health of individuals and communities. This article deals with the connection between climate change and security and the security risks that climate change poses. It elaborates on the theoretical approaches to treat climate change as a security issue and argues that climate change, which is a multidimensional problem, should be seen, inter alia, as a security issue. In this context, the article also focuses on the risks and perceptions of climate change in the Western Balkan countries.
Keywords: climate change; climate action; Western Balkans; sustainable development